Quantification of Diterpenes and their Palmitate Esters in Coffee Brews by HPLC-DAD - Marzieh Moeenfard (2015)
The present paper aimed the optimization of the saponification and extraction of diterpenes from coffee brews using a simple methodology based on HPLC-DAD, as well as to quantify the diterpenes and their palmitate esters content in several coffee brews. Regarding cafestol and kahweol, the best conditions to maximize total extraction yield were achieved through the direct saponification of 2.5 mL of coffee brew along with 3.00 g of potassium hydroxide (KOH) in a water bath (80 ºC). The proposed method consists in two sequential extractions using diethyl ether followed by a clean-up with 5 mL of 2 M NaCl solution prior to HPLC-DAD analysis to eliminate soap and co-eluting interferences. Cafestol and kahweol palmitates also were quantified using the same procedure, but without the saponification step. The proposed methods exhibited high accuracy (average recovery of 85%) and linearity (R2>0.999) and good precision (%CV<5%) with low limit of detection (less than 0.25 mg/L) and limit of quantification (less than 0.70 mg/L). Comparison of different brewing techniques revealed that capsule coffee with individual cup size of 50 mL contained the highest cafestol (1.85 mg/cup) and kahweol (2.75 mg/cup) concentration. In contrast, the lowest values of diterpenes were found in filter coffee (0.1 mg cafestol and 0.03 mg kahweol/200 mL). The higher and lower values of palmitate esters were also obtained from capsule and filter coffee, respectively. The proposed methods were simple, time saving and require low solvent consumption for quantification of diterpenes and their palmitate esters in various types of coffee brews.